Clinical Application and Mechanistic Investigation of GLP-1 Receptor Agonists in the Treatment of Polycystic Ovary Syndrome - Liu, Yan (Pacific International Journal, 2025)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine and metabolic disorder characterized by hyperandrogenism, ovulatory dysfunction, and insulin resistance, leading to significant impairment of reproductive health and overall quality of life. Recent attention has been directed toward glucagon-like peptide-1 (GLP-1) receptor agonists, a novel class of metabolic modulators, due to their potential therapeutic effects in improving insulin resistance and regulating metabolic pathways. This study aims to evaluate the clinical efficacy and underlying mechanisms of GLP-1 receptor agonists in the management of PCOS, synthesizing findings from randomized controlled trials (RCTs) and real-world studies. Our analysis demonstrates that GLP-1 receptor agonists effectively reduce body weight, alleviate insulin resistance, and enhance reproductive function in PCOS patients. These agents also decrease androgen levels, promote ovulation, and increase pregnancy rates. Mechanistic investigations suggest that GLP-1 receptor agonists exert comprehensive metabolic regulatory effects by modulating insulin signaling pathways, enhancing central appetite control, and reducing inflammatory responses. Furthermore, GLP-1 receptor agonists exhibit favorable safety profiles, with mild gastrointestinal discomfort as the primary adverse effect, and high patient adherence. In conclusion, GLP-1 receptor agonists offer a promising novel therapeutic approach for PCOS, particularly in addressing metabolic disturbances and improving reproductive outcomes. Future multicenter, large-scale RCTs are warranted to refine clinical protocols and further elucidate their mechanisms, thereby providing more tailored treatment options for PCOS patients.